How to steal a scoundrel's heart - Lorret, Vivienne (Lorret, Vivienne. Mating habits of scoundrels., 2022)
Ruined debutante Prudence Thorogood lost everything when she was ousted from polite society, including her inheritance. Now she'll do anything to take back what's hers... even if she has to steal it. Accepting a scandalous offer from Lord Savage seems like the perfect solution to disguise her criminal intentions from the ton. Until she discovers that there's more to this scoundrel than meets the eye. Leo Ramsgate, Marquess of Savage, has everything except for a heart. That organ dried up long ago after a devastating betrayal. Since then, he vowed never to trust or love again. He ensures that his dalliances are mutually satisfying, but always temporary... until he meets the reserved Miss Thorogood. Not one of his previous lovers has ever beguiled him the way she does. Not one has made him want to break his own rules. Not one has tempted him to keep her... forever. Prue has every intention of disappearing from London after their affair ends. But her plan falters when she finds herself falling hopelessly in love with a man who may never love her in return. With time running out and so much at stake, she cannot help but wonder...